Public Perceptions of Cancer Risk Factors: a Western Australian Study - MacTiernan, A.; Fritschi, Lin; Slevin, Terry; Jalleh, Geoffrey; Donovan, Robert; Heyworth, J. (Australian Health Promotion Association, 2014)
Issue addressed: People’s perceptions of risk may influence health-related behaviours. The aim of this study was to investigate the perception of cancer risk factors among Western Australian adults in order to inform health promotion policies.Methods: Cross-sectional surveys of 2094 adults were undertaken in 2007/2008 in which respondents were asked whether they thought factors increased or decreased the risk of cancer. Factors included both established and unestablished risk factors for cancer. The distribution of perceptions was compared according to age and sex.Results: The study found high levels of endorsement for some unestablished risk factors (74–91%) and comparatively lower levels of endorsement for many established risk factors (33–80%). The established risk factors of smoking and asbestos received high levels of endorsement (94–98%).Conclusion: It appears that the alignment between scientifically established risk factors and the Western Australian public’s perception of cancer risk factors could be improved.